HUBUNGAN KEMAMPUAN METAKOGNIF , SELF- REGULATED LEARNING, MOTIVASI INSTRINSIK DENGAN HASIL BELAJAR MAHASISWA PROGRAM STUDI MAGISTER ADMININSTRASI PENDIDIKAN FKIP UNIVERSITAS TANJUNGPURA - M Syukri (Jurnal Visi Ilmu Pendidikan, 2023)
AbstractThe purpose of this study is to describe the correlation between metacognitive ability, self-regulated learning, and intrinsic motivation towards learning achievement among students enrolled in a course in research methodology at the faculty of teacher training and education of  Tanjungpura University. These students are all pursuing a master's degree in education administration at the university. The research combines a quantitative approach and a correlation analysis, in its methodology. There were 58 different students that took part in the research project. In order to collect data for this research, researchers are using a questionnaire as well as records of the scores that students received on the final exam for the course. The data that was gathered from the instruments was analyzed using SPSS version 25, utilizing descriptive statistics and inferential statistics, along with product moment person and product correlation, to draw conclusions. The findings of the research indicate, in general, that a positive association exists between metacognitive capacity, self-regulated learning, and intrinsic motivation in terms of the students' overall level of academic accomplishment. The study found, more specifically, that: (1) there is a significant correlation found between metacognitive ability, self-regulated learning, and intrinsic motivation towards students' learning achievement with 1.00 perfect correlation category; (2) there is a correlation between metacognitive ability, self-regulated learning, and intrinsic motivation towards students' learning achievement; and (3) there is a correlation (2) There is a strong correlation of 0.705 between students' self-regulated learning and their overall academic achievement; (3) there is a strong correlation of 0.632 between students' intrinsic motivation and their overall academic achievement; and (4) there is a medium correlation of 0.566 between students' metacognitive ability, self-regulated learning, and overall academic achievement.                      Key Words: Metacognition, Self-Regulated Leaning, Learning Motivation, and Learning Achievement.                                     AbstrakPenelitian ini bertujuan untuk menggambarkan kemampuan metakognif , self- regulated learning, motivasi instrinksik dalam hubungannya dengan  hasil belajar  mahasiswa Program Studi Magister Admininstrasi Pendidikan  yang mengikuti perkuliahan mata kuliah  metode penelitian di FKIP Universitas Tanjungpura.    Penelitian ini menggunakan metode deskriptif dengan  pendekatan kuantitatif dan jenis penelitian  korelasional. Alat pengumpulan data utama penlitian ini berupa angket dan dokumen nilai hasil ujian mata kuliah metodelogi penelitian.  Data diperoleh dari 58 responden, kemudian dianalisis dengan statistik deskriptif dan  inferensial antara lain: product moment correlation person dan product moment melalui program aplikasi SPSS versi 25.  Secara umun penelitian ini   menyimpulkan  bahwa terdapat hubungan positif antara kemampuan metakognitif,  self-regulated learning dan motivasi insrinsik dengan hasil belajar mata kuliah  metode penelitian  pada mahasiswa program studi admininstrasi pendidikan program magister  FKIP Universitas tanjungpura. Secara khusus dapat disimpulkan, yaitu: (1) Terdapat hubungan  yang signifikan antara kemampuan metakognitif dengan hasil belajar pada mata kuliah  metode penelitian  pada mahasiswa program studi Magister Administrasi Pendidikan  FKIP Universitas tanjungpura sebesar 1,00, dengan  kategori korelasi sempurna;  (2) Terdapat hubungan  yang signifikan antara self-regulated learning dengan hasil belajar mata kuliah  metode penelitian  pada mahasiswa program studi studi Magister Administrasi Pendidikan  FKIP Universitas Tanjungpura sebesar 0,705 dengan kategori korelasi kuat.; (3)Terdapat hubungan  yang signifikan antara motivasi instrinsik dengan hasil belajar mata kuliah  metode penelitian  pada mahasiswa program studi  Magister Administrasi FKIP Universitas Tanjungpura sebesar 0,632,dengan kategori korelasi kuat;  dan (4) Terdapat hubungan secara bersama-sama antara kemampuan metakognitif dengan  self-regulated learning dan motivasi instrinsik dengan hasil  belajar mata kuliah metodelogi penelitian  pada mahasiswa program studi Administrasi Pendidikan program Magister  FKIP Universitas Tanjungpura sebesar 0,566  dengan kategori korelasi sedang.Kata Kunci: Metakognif , Self- Regulated Learning, Motivasi, Hasil  Belajar